2010
DOI: 10.1007/s11468-010-9178-z
|View full text |Cite
|
Sign up to set email alerts
|

Chemical Deposition of Silver for the Fabrication of Surface Plasmon Microstructured Optical Fibre Sensors

Abstract: We compare the Tollens reaction, a simple chemical coating method, with the more commonly used RF sputtering technique for use in creating surfaces suitable for sensing applications based on surface plasmon resonance. Experiments show that by optimising the chemical process, these two approaches can produce surfaces that exhibit similar surface plasmon resonance (SPR) performance. Thus, the Tollens method is a viable one for coating the interior surfaces of a microstructured optical fibre. As a demonstration, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
51
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 96 publications
(51 citation statements)
references
References 14 publications
(18 reference statements)
0
51
0
Order By: Relevance
“…Silver thin films of 50 nm thicknesses, previously determined to be optimal for SPs excitation [28], were deposited on standard microscope glass slides using two methods, electroless plating [28], and thermal evaporation [29]. Different deposition conditions, in particular deposition rates, were used for the thermal evaporation to vary the surface roughness of the deposited silver films [29].…”
Section: Silver Film Fabricationmentioning
confidence: 99%
See 1 more Smart Citation
“…Silver thin films of 50 nm thicknesses, previously determined to be optimal for SPs excitation [28], were deposited on standard microscope glass slides using two methods, electroless plating [28], and thermal evaporation [29]. Different deposition conditions, in particular deposition rates, were used for the thermal evaporation to vary the surface roughness of the deposited silver films [29].…”
Section: Silver Film Fabricationmentioning
confidence: 99%
“…Different deposition conditions, in particular deposition rates, were used for the thermal evaporation to vary the surface roughness of the deposited silver films [29]. Procedure reported by Boehm et al [28], was followed for fabrication of silver coatings using the electroless plating method. All substrates were thoroughly cleaned by sonication in acetone for 30 min, then rinsed with ethanol and deionized water prior silver thin film deposition.…”
Section: Silver Film Fabricationmentioning
confidence: 99%
“…Moreover it has been previously shown that the silver coating deposited using this chemical technique has the same optical properties as a silver film deposited by thermal evaporation [18] . The Tollens reaction (also known as the silver mirror reaction) consists of adding a solution of silver ammonium to a reducing agent, usually a sugar such as glucose, in order to produce silver nanoparticles that can subsequently be attached to a substrate [19] .…”
Section: Silver Electroless Platingmentioning
confidence: 85%
“…Optical-fiber-based SPR sensors have more advantages over conventional prism-based SPR sensors, particularly in terms of flexibility and cost . Currently, opticalfiber-based SPR sensors have been widely used in chemical sensors (Boehm et al, 2011) and gas sensors (Kim et al, 2005;Wang et al, 2013).…”
Section: Spr Biosensorsmentioning
confidence: 99%